Diseases Characteristic of Pre-Weaning Bali Calf (Bos Javanicus) in Central Lombok, Indonesia - Adji Santoso Dradjat; Muhamad Imran; T.S. Panjaitan; Dahlanuddin Dahlanuddin (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2018)
The aim of the study was to evaluate Bali cattle pre-weaning calf death in Central Lombok. Sick calves were examined their condition, followed by physiology examination. Then feces and blood samples were collected and examined for internal parasites and hematology. The results showed that the newborn calf was 57,2% (61), while calves sick was 16.5% (101) consisted of 7,2% (57) death calves and 9,3% still alive. Calves examination showed that 21, 05 % (12) was under weak conditions, 38.5% (22) with high temperature, 73, 5% (42) calves were found diarrhea. This diarrhea calves consisted of 50,8% (29) diarrhea, 3, 5% (2) diarrhea with blood stain, and 19, 2% (11) diarrhea with high temperature. The results of coproscopy showed that 14.03% (8) calves diarrhea were infected with parasites, such as protozoa (Eimeria sp), liver fluke (Fasciola sp) and gastro intestine worm (Trichuris sp, Trichostrongilus sp, and Bunostonum sp). Following evaluation of hematocrit, it was found that 33.3% (19) calves higher while 3.50% (2) lower. Following examination of Red Blood Cell, it was found that 98.2% (56) calves showed anemia hypochromic, 28.07% (16) showed anemia microcytic, 15,7% (9) macrocytic anemia, 5.2% (3) anemia hypochromic, 3.5% (2 calves) showed erythropenia. Leucocytes examinations showed that 35.08% (20 calves) showed by lymphocytosis, 7.01% (4 calves) leucocytosis, 1.75% (1 calf) leucopenia and 1.75% (1 calf) lymphocytopenia. It can be concluded that from the ill calves in the middle of the rainy season showed diarrhea with protozoa, liver fluke, and worms infestations. Hematology examination the sick calves indicated that there were anemia, lymphocytosis, dehydration, low content of blood corpuscular. Finally, the sick calves may be infected with parasites, protozoa’s, bacteria’s and viruses.